Influence of metabolic therapy on life quality in patients with atrial fibrillation paroxysms - Fushtey, I. M.; Podsevahina, S. L.; Palamarchuk, A. I.; Chabanna, E. S.; Фуштей, Іван Михайлович; Подсевахіна, Світлана Леонтіївна; Паламарчук, Олександр Іванович; Чабанна, Олена Сергіївна (My University, 2022)
Purpose of the study. The goal of the study was to investigate the effect of magnesium orotate as a part of complex therapy in sinus rhythm restoring in patients with AF paroxysm, as well as to evaluate its effectiveness and effect on LQo with long-term use. Materials and research methods. We examined 56 patients (16 women and 40 men) with an average age of (61,5 ± 4,3) years with paroxysmal atrial fibrillation. All patients were divided into two groups. Patients of the 1st group (n = 28) underwent medical cardioversion with amiodarone and magnesium orotate. Patients of the 2nd group (n = 28) received only amiodarone. The time of sinus rhythm restoration, parameters of electrical instability of the atrial and ventricular myocardium after sinus rhythm restoration, patients life quality 3 months after discharge – were assessed in both groups. Мета дослідження. Вивчити вплив препарату оротату магнію у складі комплексної терапії при відновленні синусового ритму у хворих із пароксизмом фібриляції передсердь, а також оцінити його ефективність та вплив на якість життя при тривалому використанні. Матеріали та методи дослідження. Обстежено 56 пацієнтів (16 жінок та 40 чоловіків) середній вік, яких склав (61,5 ± 4,3) рік із пароксизмом фібриляції передсердь. Усі пацієнти були розподілені на дві групи. Пацієнтам 1-ї групи (n = 28) проводилася медикаментозна кардіоверсія аміодароном та призначався оротат магнію. Пацієнти 2-ї групи (n = 28) отримували лише аміодарон. Оцінювали час до відновлення синусового ритму в обох групах, електричну нестабільність міокарда передсердь та шлуночків після відновлення синусового ритму, якість життя пацієнтів через 3 місяці після виписки.
Вплив метаболічної терапії на якість життя хворих з пароксизмами михопітної атритії
Keywords: atrial fibrillation; medical cardioversion; amiodarone; magnesium orotate; life quality; фібриляція передсердь; медикаментозна кардіоверсія; аміодарон; оротат магнію; якість життя